KNOWLEDGE, SUFFERING AND THE PERFORMANCE OF WISDOM IN SOLON'S ELEGY TO THE MUSES AND THE BABYLONIAN POEM OF THE RIGHTEOUS SUFFERER. (December 2019) - Johnston, Alexandre
Abstract : This article offers a comparative reading of Solon's Elegy to the Muses (fragment 13 West) and the Babylonian Poem of the Righteous Sufferer, focusing on the interplay of literary form and theological content. It argues that in both poems, shifts in the identity and perspective of the poetic voice enable the speaker to act out, or perform, a particular vision of humanity and its relationship with the divine. The comparative analysis improves our understanding of both texts, showing for instance that Solon's elegy is a highly sophisticated attempt to articulate a coherent vision of divine justice and the human condition. It also sheds light on the particular modes in which ancient literature and theology interact in different contexts, and how this interaction could affect audiences.